Comparative Analysis of Short-Term Outcomes in Thoracoscopic Minimally Invasive Versus Traditional Mitral Valve Replacement: Randomized Clinical Trial Study - Shieba, Yusuf; Shalaby , Abd Elhalim; Elbanna, Tamer; Elgamal, Mohamed-Adel; El-minshawy, Ahmed (AL-Kindy College Medical Journal, 2025)
Background: The standard approach for mitral valve surgery was a sternotomy, but with the new trends, mitral valve surgery can now be performed with right mini thoracotomy incision. Minimally invasive mitral valve surgery has demonstrated superior cosmetic outcomes, less surgical trauma, shortened intensive care unit and hospital stays, cost effectiveness, and faster recovery, while the efficacy is comparable to conventional sternotomy. Objective: The aim of this research is to investigate the short-term outcomes of thoracoscopic minimally invasive mitral valve replacement in comparison with the conventional technique. Subjects and Methods: This study included 100 patients with isolated mitral valve disease, who were randomly divided into two equal groups. Group A underwent a right anterolateral video-assisted mini-thoracotomy, while Group B was approached via a conventional median sternotomy. Results: The minimally invasive group had significantly longer total operative time (291.3±48.89 min vs. 227.68±49.18 min, p = 0.001). However, Group A demonstrated better post-operative outcomes, including shorter ICU stay (2.1±1.07 vs. 3.82±1.49 days, p = 0.002), shorter extubation time (4.24±1.12 vs. 8.45±4.55 hours, p = 0.0001), reduced post-operative blood loss (271.7±107.09 ml vs. 449.2±230.93 ml, p < 0.0001). Post-operative pain scores were significantly lower in Group A (VAS 3.84±1.53 vs. 7.58±1.62, p < 0.0001), and hospital stay was shorter (7.22±1.37 vs. 11.21±3.53 days, p < 0.0001). Conclusions: Minimally invasive mitral valve surgery can be a safe and effective alternative to traditional MVS in patients with mitral valve disease.